FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR SUSU INDONESIA - Syarifah Amaliah; Idqan Fahmi (Jurnal Manajemen & Agribisnis, 2007)
The condition of excess demand that is happening to the milk commodity is the result of the low capacity in domestic milk production that has made Indonesia faced with the option of importing milk. The rise in volume of imported milk that occurred after the remission of the import ratio policy indicates that domestic milk competitiveness is low. Quantitative analysis using Engle-Granger Co-integration and Error Correction Model (ECM) to analyze factors influencing imported milk for the long-term and the short-term through one-way comparison produced a crucial research implication towards the increase of domestic milk production for the short-term. On the other hand, for the long-term, real price for domestic milk holds a key role in increasing competitiveness. The remission of the import ratio policy as an act to minimize trade restriction basically increases import volume, nevertheless it is thought that it can be overcome with an exit strategy of increasing domestic milk production for the short-term.